Development of low-cost and enhanced carbon-based electrodes for electrochemical sensors and biosensors applications - Ataide, Vanessa Neiva de (2023)
This thesis will present and discuss low-cost carbon-based electrochemical sensor fabrication strategies for applications such as sensors and biosensors. Chapter 1 presents the fabrication of paper-based electrochemical devices by the pencil-drawing technique, in which conductive carbon tracks were transferred to the paper\'s surface using a commercial drawing pencil. The electrochemical performance towards different redox probes (potassium ferrocyanide, hexaammineruthenium chloride, and ascorbic acid) was improved by activating this surface using a CO2 laser. Electrode surfaces painted using pencil drawings were characterized by chemical, electrochemical, and physical techniques and applied in detecting furosemide in synthetic urine samples. Chapter 2 describes the fabrication of carbon and thermoplastic composite electrodes activated by CO2 laser for biomolecule immobilization. The laser parameters for activating these surfaces were optimized, including power, scanning speed, resolution, and number of laser passes. Furthermore, the surface of the electrodes before and after activation was characterized by various techniques, as mentioned in the characterization of the pencil-drawing electrodes discussed in Chapter 1. These thermoplastic electrodes were applied for SARS-CoV-2 N protein detection as a proof of concept. Chapter 3 shows the fabrication of microfluidic devices coupled with electrodes for SARS-CoV-2 virus N protein detection in nasal swab samples. Several parameters for immunosensor assembly were optimized, such as biomolecule immobilization approaches, capture antibody concentrations, and the blocking step. A calibration curve was obtained in static mode ranging from 275 to 11000 PFU mL-1. Also, the layout and fabrication strategies of the microfluidic device were studied.